KAJIAN MITIGASI KONGESTI BANDARA - Anwar, Fadrinsyah; Pradono, Pradono; Purboyo, Heru; Tamin, Ofzar Z. (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The increasing of air transportation traffic that is beyond the existing airport capacity leads to the airport congestion problem. Handling the airport congestion problem can be done by increasing the airport capacity. There are many studies conducted to assess airport capacity. This study used a different approach in analyzing the airport capacity. We use subjective approach that explore the perception of managers as the actors involved in the decision-making process. By using the theory of probabilistic causality, we analyzed the factors that contribute in increasing the capacity of the airport, as well as the impact on the costs and the benefits. This paper is limited to the descriptive analysis, as the basis for further studies.